Long-term distress throughout one’s life: health-related quality of life, economic and caregiver burden of patients with neurofibromatosis type 1 in China - Liang, Wanxian; Cao, Shihuan; Suo, Yusi; Zhang, Lining; Yang, Lujia; Wang, Ping; Wang, Hanfei; Wang, Han; Bai, Guannan; Li, Qingnan; Zheng, Jiayin; Jin, Xuejing (Frontiers in Public Health, 2024)
Introduction Neurofibromatosis type 1 (NF1) is a rare genetic disorder, with lack of evidence of disease burden in China. We aimed to describe the economic burden, health-related quality of life (HRQL), and caregiver burden of NF1 patients in China. Methods We conducted an online cross-sectional survey employing the China Cloud Platform for Rare Diseases, with 223 caregivers of NF1 pediatric patients (patients under 18), and 226 adult patients. Economic burden was estimated using direct and indirect costs related to NF1 in 2021, and the Work Productivity and Activity Impairment Questionnaire: General Health V2.0 (WPAI-GH). HRQL measures included EQ-5D-Y proxy version and PedsQL™ 4.0 Generic Core Scales (PedsQL GCS) proxy version for pediatric patients, and EQ-5D-5L and PedsQL™ 3.0 Neurofibromatosis Module (PedsQL NFM) for adult patients. Caregiver burden was estimated by Zarit Burden Interview (ZBI). Results For pediatric patients, the average direct cost in 2021 was CNY 33,614 (USD 4,879), and employed caregivers’ annual productivity loss was 81 days. EQ-5D-Y utility was 0.880 ± 0.13 and VAS score was 75.38 ± 20.67, with 52.6% patients reporting having problems in “pain/discomfort” and 42.9% in “anxiety/depression.” PedsQL GCS total score was 68.47 ± 19.42. ZBI score demonstrated that 39.5% of caregivers had moderate-to-severe or severe burden. For adult patients, average direct cost in 2021 was CNY 24,531 (USD 3,560). Patients in employment reported an absenteeism of 8.5% and presenteeism of 21.6% according to the results of WPAI-GH. EQ-5D-5L utility was 0.843 ± 0.17 and VAS score was 72.32 ± 23.49, with more than half of patients reporting having problems in “pain/discomfort” and “anxiety/depression” dimensions. PedsQL NFM total score was 68.40 ± 15.57. Conclusion Both pediatric and adult NF1 patients in China had a wide-ranging economic burden and low HRQL, especially in the psychological dimension. Caregivers for NF1 pediatric patients experienced considerable caregiver burden. More attention and support from policymakers and stakeholders are required to relieve NF1 patients’ and caregivers’ distress.